Representasi Stereotype Laki-laki dalam Lirik Lagu The Lucky Lacky “Aku Bukanlah Superman” - Luthfi Hanif Fakharoenvissa; Rini Sulastri (UIN Sunan Gunung Djati Bandung, 2024)
Music is an expression of feelings expressed through writing and tones. This article explores the relationship between music, gender, and social representation in song lyrics, with a focus on the song